Sentiment Analysis of Microtakaful Industry: Comparison between Indonesia and Malaysia - Aam Slamet Rusydiana; Irman Firmansyah; Lina Marlina (UIN Sunan Gunung Djati Bandung, 2018)
It is important to do research on public sentiment towards microtakaful presence in a country in order to know public response to its existence. This study aimed to determine public sentiment towards microtakaful in Indonesia and in Malaysia. Data were collected from 40 articles, journals and other writings. Data were analyzed using the software Semantria as an analytical tool in the form of text. The results showed that the assessment of existence of microtakaful in Indonesia amounted to 52% of the community showed positive sentiment, 28% indicate negative sentiment and 20% indicates a neutral sentiment. While in Malaysia that 62% showed positive sentiment, 23% negative sentiment and 15% neutral sentiment.